STRATEGI IMPLEMENTASI COMPUTATIONAL THINKING DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: A SYSTEMATIC LITERATURE REVIEW - Farhan Zakky Ramadhan; Siti Nurhaziza; Aulia Safitri; Darwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Computational Thinking has become one of the key competencies required in 21st century education, particularly at the elementary school level, as it promotes logical, systematic, and problem-solving skills. This study aims to examine the implementation of Computational Thinking in elementary education through a Systematic Literature Review. The literature search was conducted using Google Scholar with predetermined keywords. A total of 1.780 articles were initially identified, of which 45 articles remained after the screening process. Following the application of the inclusion and exclusion criteria, 23 articles were selected for in depth analysis. The review reveals that the implementation of Computational Thinking contributes to the development of students’ abilities in decomposition, pattern recognition, abstraction, and algorithmic thinking. The findings also indicate that Computational Thinking is more effective when integrated with instructional approaches such as Problem Based Learning, Project Based Learning, and Inquiry Learning, as well as supported by learning media including Scratch, Artificial Intelligence, and Gamification. Overall, the findings suggest that Computational Thinking is an effective instructional approach for strengthening elementary school students’ Computational Thinking skills while fostering the competencies needed in the 21st century.